2020
DOI: 10.3389/fpls.2020.00453
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping and Data Mining to Identify Genes Associated With the Sinorhizobium fredii HH103 T3SS Effector NopD in Soybean

Abstract: In some legume-rhizobium symbioses, host specificity is influenced by rhizobial type III effectors-nodulation outer proteins (Nops). However, the genes encoding host proteins that interact with Nops remain unknown. In this study, we aimed to identify candidate soybean genes associated with NopD, one of the type III effectors of Sinorhizobium fredii HH103. The results showed that the expression pattern of NopD was analyzed in rhizobia induced by genistein. We also found NopD can be induced by TtsI, and NopD as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…A QTL mapping study in soybean recombinant inbred lines (RILs) involving a symbiosis with Sinorhizobium fredii HH103 rhcJ mutant, which resulted in a reduced nodule number, identified three host genes that might be participating in the reduction process (Zhu et al, 2019). Another protein, NopD, which is one of the type III effectors of S. fredii, influences the expression of two genes associated with two QTLs (Wang et al, 2020b). These interactions resulted in nodule phenotypic differences in soybean RILs.…”
Section: Snf-associated Qtls and Snpsmentioning
confidence: 99%
“…A QTL mapping study in soybean recombinant inbred lines (RILs) involving a symbiosis with Sinorhizobium fredii HH103 rhcJ mutant, which resulted in a reduced nodule number, identified three host genes that might be participating in the reduction process (Zhu et al, 2019). Another protein, NopD, which is one of the type III effectors of S. fredii, influences the expression of two genes associated with two QTLs (Wang et al, 2020b). These interactions resulted in nodule phenotypic differences in soybean RILs.…”
Section: Snf-associated Qtls and Snpsmentioning
confidence: 99%
“…The QTL and candidate genes underlying the symbiosis-related traits were identified in recombinant inbred lines (RILs) based on a linkage map with SNP markers. The responses of QTL to NopL, NopP, and NopD have been studied (Wang et al 2018;Zhang et al 2018;Wang et al 2020). Although previous research has identified several QTL associated with symbiosis-related traits in soybean, more work is needed to identify the genes involved in QTL responses to different T3Es.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that among the cocktail of T3Es secreted, SkP48 is most probably recognised by Rproteins, thereby inhibiting infection and/or nodulation to a greater or lesser extent. As previously mentioned, some SUMO proteases and SKs have been reported to act as negative T3Es in plant hosts 9,[26][27][28] , raising the possibility that DOA9 SkP48 responsible for this incompatibility can be either one or both protein domains (SUMO protease and/or SK domain).…”
Section: Discussionmentioning
confidence: 96%